PENGEMBANGAN KOMIK â€œDUMADINE DESA KELETâ€ SEBAGAI MEDIA PEMBELAJARAN TEKS CERITA RAKYAT KELAS VII - sari, fitriana (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2019)
The lack of intructional media that is appropriate to social and cultural bagrounds becomes the basis for the need to develop learning by developing lesson plans and comic media as supporting media. The research method uses a research and development approach with five stages, including identification of potential and problems, data collection, product design, design validation, and design revisions. Data collection instruments include abservation guides, interview guides, needs questionnaires, material. Product design contains narration, images and description of the story â€œDumadine Desa Keletâ€ the validation results show an average media expert. Overall the product validation test result show and average media expert, a score of 3,2 fron the material expert. Overall the product validation test results show an average score of 3, which means the product design is the good rating category.